2021
DOI: 10.3390/polym13050719
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Comparison of Melt-Blowing Airflow Fields: Nozzle Modifications to Reduce Turbulence and Fibre Whipping

Abstract: In the melt-blowing process, micro/nanofibrous nonwovens are attenuated and formed through aerodynamic force in a turbulent airflow field. In this work, two types of airflow-directors were added under a common melt-blowing slot-die nozzle to obtain modified airflow fields. The effect of airflow-directors on time-averaged characteristics, turbulence intensity, and temperature fluctuation intensity are achieved through the simultaneous measurement of fluctuating velocity and fluctuating temperature using a two-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(48 reference statements)
3
8
0
Order By: Relevance
“…8,59 However, after exiting the orifice, although the fiber diameter is too large to undergo any bending motion, it is still susceptible to the growth of minor oscillations along its surface. 42,55,60 An interesting study by Sun et al found that for high air velocities (280 m/s), the whipping amplitude increases further from the die, but low air velocities (110 m/s) show a rapid increase in whipping amplitude near the die exit, which then decays rapidly further downstream. 61 An approach to minimize fiber whipping is to minimize the spread of the air flow field through the use of a solid boundary to guide the fiber and air flow.…”
Section: ■ Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…8,59 However, after exiting the orifice, although the fiber diameter is too large to undergo any bending motion, it is still susceptible to the growth of minor oscillations along its surface. 42,55,60 An interesting study by Sun et al found that for high air velocities (280 m/s), the whipping amplitude increases further from the die, but low air velocities (110 m/s) show a rapid increase in whipping amplitude near the die exit, which then decays rapidly further downstream. 61 An approach to minimize fiber whipping is to minimize the spread of the air flow field through the use of a solid boundary to guide the fiber and air flow.…”
Section: ■ Overviewmentioning
confidence: 99%
“…58 Adding an outerdirector to a slot die (marked red in Figure 21) can decrease air velocity fluctuations, which can suppress fiber oscillations and minimize whipping. 60 If the turbulent nature of fiber whipping can be understood and controlled, it could potentially be used to further attenuate the fibers to smaller diameters. 61 Verifying Fiber Simulations with Experiments.…”
Section: ■ Overviewmentioning
confidence: 99%
See 3 more Smart Citations